THE ROLE OF MANAGEMENT ACCOUNTING IN THE DECISION MAKING PROCESS: CASE STUDY CARAŞ SEVERIN COUNTY - BREUER, Adela; FRUMUȘANU, Mihalea Lesconi; MANCIU, Andra (Annales Universitatis Apulensis Series Oeconomica, 2013)
Management accounting is an important part of the economic information system, with a key role in decision making, whether we talk about small and medium enterprises or large companies. However, management accounting is superficially treated in most economic entities, there are entities in which professional accountants consider management accounting as optional, as shown in the survey performed in Caraş Severin County, querying 50 economic entities from the three categories (microenterprises, SMEs and large companies) and processing the results in SPSS.